A colorimetric approach for measuring mercuric ions with high selectivity using label-free gold nanoparticles and thiourea1. Issue 16 (21st August 2015) - Wang, Qianru; Li, Yiran; Li, Min; Wen, Congying; Liu, Rongsheng; Subhan, Fazle; Yan, Zifeng; Zeng, Jingbin
<x xml:space="preserve">Abstract</x> A simple, sensitive and selective colorimetric assay was developed for detecting Hg2+ by coupling Au NPs with thiourea.